The conserved genetic program of male germ cells uncovers ancient regulators of human spermatogenesis - Brattig-Correia, Rion (2024)
National Institutes of Health (1R01LM012832) National Science Foundation (Research Traineeship grant 1735095). Deutsche Forschungsgemeinschaft (329621271). Ministry of Education, Singapore (MOE2018-T2-2-053). Publisher Copyright: © 2024, Brattig-Correia, Almeida, Wyrwoll et al.